PENGARUH MOTIVASI KERJA TERHADAP DISIPLIN GURU SMK LABOR BINAAN FKIP UNRI PEKANBARU - Rahmi, Rizky Alvi; Johan, Rina Selva; ', Hendripides (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstack: This research aims to find out the influence of Work Motivation on disippline. The population in this study are all teachers SMK Labor Binaan FKIP UNRI Pekanbaru, which is defined as samples taken by using saturated sampling technique. Data were collected using a questionnaire or questionnaires and documentation. Data were analyzed using simple regression analysis and F test with significance level of 0.05%. The result showed that motivation work simultaneously positive and significant impact on teacher discipline. It is based on the analysis results, which show the calculation results F count> F table (6.064> 4.16). and the amount of contributions or donations to the Discipline Work Motivation show with great determination only by 16.3% (R Square 0.163) while the remaining 83.7% is influenced by other factors not examined in this study.Keywords: Motivation, Discipline